Lifetime productivity and repeatability estimation of selected traits of crossbred cows in Savar Dairy Farm (Progressive Agriculture, 2018)
The study was conducted on 244 crossbred cows of (Central Cattle Breeding and Diry Farm), Savar, Dhaka to evaluate the effect of different productive groups on their lifetime performance of various productive traits using twenty years data.  Data were accumulated from a prescribed data sheet maintained by Central Cattle Breeding Station, Savar, Dhaka. Genetic groups for this experiment were Local Friesian (LF), Local Jersey (LJ), Local Hariana X Friesian (LH x F), Local Friesian X Local Friesian (LF x LF) and Local Jersey X Local Jersey (LJ x LJ). The studied parameters were age at puberty, lactation length, lactation yield, total milking days, and total milk yield in lifetime. The data were analyzed using Least-Squares Mixed Model and Maximum Likelihood Computer Program (Harvey, 1990). Analysis showed that genetic groups had a significant effect on age at puberty, lactation length and lactation yield (P